2022
DOI: 10.3389/fonc.2021.691112
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Comprehensive Morphological and Radiomics Features of Subsolid Pulmonary Nodules to Distinguish Minimally Invasive Adenocarcinomas and Invasive Adenocarcinomas in CT Scan

Abstract: ObjectiveTo investigative the diagnostic performance of the morphological model, radiomics model, and combined model in differentiating invasive adenocarcinomas (IACs) from minimally invasive adenocarcinomas (MIAs).MethodsThis study retrospectively involved 307 patients who underwent chest computed tomography (CT) examination and presented as subsolid pulmonary nodules whose pathological findings were MIAs or IACs from January 2010 to May 2018. These patients were randomly assigned to training and validation g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Cetin et al [ 26 ] demonstrated the feasibility and the clinical value of the cardiac MRI radiomics in analyzing the cardiovascular risk factors including diabetes, hypertension, high cholesterol, and smoking. Moreover, Lu et al [ 27 ] proposed a combined model, including morphological features and radiomics features from CT scan, to distinguish minimally invasive adenocarcinomas and invasive adenocarcinomas, with high potential to provide for the auxiliary diagnosis. Therefore, if hundreds of thousands of features could be extracted from images by radiomics, and features extraction and dimension reduction can be performed on them, then the performance of the regression and classification model in our study may be better.…”
Section: Discussionmentioning
confidence: 99%
“…Cetin et al [ 26 ] demonstrated the feasibility and the clinical value of the cardiac MRI radiomics in analyzing the cardiovascular risk factors including diabetes, hypertension, high cholesterol, and smoking. Moreover, Lu et al [ 27 ] proposed a combined model, including morphological features and radiomics features from CT scan, to distinguish minimally invasive adenocarcinomas and invasive adenocarcinomas, with high potential to provide for the auxiliary diagnosis. Therefore, if hundreds of thousands of features could be extracted from images by radiomics, and features extraction and dimension reduction can be performed on them, then the performance of the regression and classification model in our study may be better.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that LargeDependenceEmphasis, a radiomics feature from GLDM, can exhibit robust performance in discriminating lung cancer from tuberculosis with an AUC of 0.92 ( 36 ). GLCM describes the integrated information about spatial correlation characteristics of pixel pairs in terms of the pattern of grayscale arrangement, direction, distance, and gray value ( 37 ). Notably, textural features derived from GLCM have been demonstrated to have pathological association and can be applied to the diagnosis of malignant lesion in breast cancer ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, software-based analysis of lung nodules is very promising and is attracting great interest, not only among thoracic radiologists but also among other thoracic physicians. Among software-based methods applied to SSNs, those related to the prediction of histological invasiveness of resected SSNs are widely described in the literature [ 35 39 ], whereas those related to the prediction of growth are few and have been investigated almost exclusively in Asian populations [ 22 27 , 30 , 41 ].…”
Section: Discussionmentioning
confidence: 99%